The Potential of MOOCs for Large-Scale Teacher Professional Development in Contexts of Mass Displacement - Kennedy, Eileen; Laurillard, Diana (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Publisher: UCL IOE Press KerkoCite.ItemAlsoKnownAs: 2129771:7VCJER7N
Keywords: Access to Education; Blended Learning; Children; Developing Nations; Faculty Development; Foreign Countries; Handheld Devices; Instructional Design; Instructional Effectiveness; Internet; Online Courses; Public Schools; Refugees; Sustainability; Teacher Collaboration; Teacher Educators; Teachers; Telecommunications; Vocational Education; Workshops; __C:filed:1; ⛔ No DOI found